Analisis Mobilitas Node Jaringan Nirkabel Pada Software Defined Wireless Network (SDWN) - Putri Rizqia Hardein; Rakhmadhany Primananda; Achmad Basuki (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Software Defined Network (SDN) has been developed over the last few years with the aim to simplify complexity in computer network. SDN's concept also developed to other kind of computer network including wireless network that really popular nowadays. The popularity of wireless network is caused by the simplicity and mobility that possible so there is no limitation for user's movement. But in the other hand, mobility also adds more challenges and really effected to the quality of wireless network performance. So, mobility is an important factor to considered when measuring wireless network performance. In this research, analysis of node mobility in SDN-wireless based or Software Defined Wireless Network (SDWN) has been done. The analysis is done by measuring network performance metrics specifically throughput, packet loss, and delay with Random Direction, Random Walk, and Random Way Point mobility model. The measurement is done at different velocity of node that is 5m/s, 10m/s, 15m/s, 20m/s, and 25m/s. The result shows that the highest throughput value 9.63 Mbps is gain in Random Direction at maximum velocity 25m/s, but it shows different result when the test is redone with 6.46 Mbps as highest throughput in Random Way Point that is caused by the instability of emulator. In the other hand, Random Way Point has the lowest packet loss 2116.2 packets at 25m/s and the lowest delay 51.056ms at 20m/s. The results show unstable value because of the emulator instability.